PENDAMPINGAN MANAJEMEN KUALITAS AIR DAN APLIKASI PROBIOTIK PADA BUDIDAYA IKAN LELE PONDOK DARUL MUKMIN, SUKOREJO, PASURUAN JAWA TIMUR - Dewi, Nina Nurmalia; Satyantini, Woro Hastuti; Isroni, Wahyu; Mahasri, Gunanti; Manan, Abdul; Cahyoko, Yudi; Wisudyawati, Dita (LPPM Universitas Al Muslim, 2024)
Pasuruan Regency is one of the regencies that has potential in the fisheries sector, especially freshwater fisheries cultivation. The potential area for cultivation activities is located in Sukorejo District with the cultivated commodity being catfish. One of the farmer groups in Sukorejo District is the Pondok Darul Mukmin Sangkuriang Catfish farmer. However, this catfish cultivation activity has not been running optimally, because the cultivation system used is still traditional. This community service activity aimed to provide assistance related to water quality management and probiotic application in catfish cultivation. This activity was carried out at Pondok Darul Mukmin from July to September 2024. The method of implementing the activity was in the form of training, assistance, and demonstrations of water quality management, probiotic application in feed, and probiotic culture for catfish cultivation. The results of this community service activity showed that Pondok Darul Mukmin fish farmer were very enthusiastic in participating in the training activities. In addition, the community can also carry out catfish cultivation by monitoring water quality and applying probiotics to feed. Cultivation activities resulted in increased catfish growth every week.